John Ruskin and the Victorian Theatre - Newey, K. author. aut Link
X, 257 p.
Keywords: This is the first book to explore the involvement of John Ruskin with the popular theatre of his time. Based on original archival research, this book offers a fresh look at the aesthetic and social theories of Ruskin and his direct and indirect influence on the commercial theatre of the late nineteenth century.